Extractive electrospray ionization mass spectrometry for analytical evaluation and synthetic preparation of pharmaceutical chemicals - Qin, Manman; Qian, Yuqing; Huang, Lu; Zhong, Chao; Li, Mingdong; Yu, Jun; Chen, Huanwen (Frontiers in Pharmacology, 2023)
Extractive Electrospray Ionization Mass Spectrometry (EESI-MS) has been widely used in high throughput analysis of the integral component, pharmacokinetics, quality control and synthesis of pharmaceutical chemicals due to its unique configuration of the ionization assembly, which enables the effective ionization of the trace amount of molecules of interest in samples containing a complex matrix with high sensitivity, specificity and fast response and allows the energetic molecular species to undergo dedicatedly designed reaction for advanced functionalization. The typical effect of operation conditions on the analytical performance of EESI-MS for various pharmaceutical compounds, different pharmaceutical preparations, and herb medicine materials has been systematically reviewed. The perspective of EESI application in unusual functionalization of molecules for advanced pharmaceutical chemicals is also briefly described.